Agent Based Simulation for a Sustainable Society and Multiagent Smart Computing International Workshops, PRIMA 2011, Wollongong, Australia, November 14, 2011, Revised Selected Papers - Cranefield, Stephen.; Cranefield, Stephen.; Song, Insu.; Song, Insu. (Lecture Notes in Artificial Intelligence ;, 2012)
This book constitutes the refereed proceedings of the two workshops held at the 14th International Conference on Principles and Practice of Multi-Agent Systems, PRIMA 2011, held in Wollongong, Australia, in November. The workshops were, Workshop on Agent Based Simulation for a Sustainable Society (ABSSS 2011) and International Workshop on Multi-Agent Smart Computing (MASmart 2011). The 8 papers presented were carefully reviewed and selected from various submissions. The papers cover topics from agent based simulation for a sustainable society and on multi-agent smart computing.